Gasotransmitters: Potential Therapeutic Molecules of Fibrotic Diseases. (21st September 2021) - Chen, Yingqing; Yuan, Shuo; Cao, Yuying; Kong, Guangyao; Jiang, Feng; Li, You; Wang, Qi; Tang, Minli; Zhang, Qinggao; Wang, Qianqian; Liu, Liping
Abstract : Fibrosis is defined as the pathological progress of excessive extracellular matrix (ECM), such as collagen, fibronectin, and elastin deposition, as the regenerative capacity of cells cannot satisfy the dynamic repair of chronic damage. The well-known features of tissue fibrosis are characterized as the presence of excessive activated and proliferated fibroblasts and the differentiation of fibroblasts into myofibroblasts, and epithelial cells undergo the epithelial-mesenchymal transition (EMT) to expand the number of fibroblasts and myofibroblasts thereby driving fibrogenesis. In terms of mechanism, during the process of fibrosis, the activations of the TGF- β signaling pathway, oxidative stress, cellular senescence, and inflammatory response play crucial roles in the activation and proliferation of fibroblasts to generate ECM. The deaths due to severe fibrosis account for almost half of the total deaths from various diseases, and few treatment strategies are available for the prevention of fibrosis as yet. Recently, numerous studies demonstrated that three well-defined bioactive gasotransmitters, including nitric oxide (NO), carbon monoxide (CO), and hydrogen sulfide (H2 S), generally exhibited anti-inflammatory, antioxidative, antiapoptotic, and antiproliferative properties. Besides these effects, a number of studies have reported that low-dose exogenous and endogenous gasotransmitters can delay and interfere with the occurrence and development of fibrotic diseases, including myocardial fibrosis, idiopathic pulmonary fibrosis, liver fibrosis, renal fibrosis, diabetic diaphragm fibrosis, and peritoneal fibrosis. Furthermore, in animal and clinical experiments, the inhalation of low-dose exogenous gas and intraperitoneal injection of gaseous donors, such as SNAP, CINOD, CORM, SAC, and NaHS, showed a significant therapeutic effect on the inhibition of fibrosis through modulating the TGF- β signaling pathway, attenuating oxidative stress and inflammatory response, and delaying the cellular senescence, while promoting the process of autophagy. In this review, we first demonstrate and summarize the therapeutic effects of gasotransmitters on diverse fibrotic diseases and highlight their molecular mechanisms in the process and development of fibrosis.